Understanding Rack-Scale Disaggregated Storage - Legtchenko, Sergey; Williams, Hugh; Razavi, Kaveh; Donnelly, Austin; Black, Richard; Douglas, Andrew; Cheriere, Nathanael; Fryer, Daniel; Mast, Kai; Brown, Angela Demke; Klimovic, Ana; Slowey, Andy; et al. (9th USENIX Workshop on Hot Topics in Storage and File Systems (HotStorage '17), 2017)
Disaggregation of resources in the data center, especially at the rack-scale, offers the opportunity to use valuable resources more efficiently. It is common that mass storage racks in large-scale clouds are filled with servers with Hard Disk Drives (HDDs) attached directly to each of them, either using SATA or SAS depending on the number of HDDs. What does disaggregated storage mean for these racks? We define four categories of in-rack disaggregation: complete, dynamic elastic, failure, and configuration disaggregation. We explore the benefits and impact of these design points by building a highly flexible research storage fabric, that allows us to build example systems that embody the four designs.